Stuttering in individuals with Down syndrome: a systematic review of earlier research - Hokstad, Silje; Næss, Kari-Anne B. (Frontiers in Psychology, 2023)
The main objective of this systematic review was to synthesize the evidence on the occurrence and characteristics of stuttering in individuals with Down syndrome and thus contribute knowledge about stuttering in this population. Group studies reporting outcome measures of stuttering were included. Studies with participants who were preselected based on fluency status were excluded. We searched Eric, PsychInfo, Medline, Scopus, and Web of Science core collection on January 3rd, 2022, and conducted supplementary searches of reference lists of previous reviews and the studies included in the current review, as well as relevant speech and language journals. The included studies were coded in terms of information about sample characteristics, measurement approaches, and stuttering-related outcomes. The appraisal tool for cross sectional studies (AXIS) was used to evaluate study quality. We identified 14 eligible studies, with a total of 1,833 participants (mean = 131.29, standard deviation = 227.85, median = 45.5) between 3 and 58 years of age. The estimated occurrence of stuttering ranged from 2.38 to 56%, which is substantially higher than the estimated prevalence (1%) of stuttering in the general population. The results also showed that stuttering severity most often was judged to be mild to moderate and that individuals with Down syndrome displayed secondary behaviors when these were measured. However, little attention has been paid to investigating the potential adverse impacts of stuttering for individuals with Down syndrome. We judged the quality of the evidence to be moderate to low. Negative evaluation was mostly due to sampling limitations that decreased the representability and generalizability of the results. Based on the high occurrence of stuttering and the potential negative impacts of this condition, individuals with Down syndrome who show signs of stuttering should be referred to a speech and language pathologist for an evaluation of their need for stuttering treatment. Key words: Down syndrome, stuttering, systematic review, speech, disfluency, stuttering assessment